A Hub Matrix Theory and Applications to Wireless Communications. (6th May 2007) - Kung Kung, H. T. H. T.; Suter Suter, B. W. B. W.
Abstract : This paper considers communications and network systems whose properties are characterized by the gaps of the leading eigenvalues ofA H A for a matrixA . It is shown that a sufficient and necessary condition for a large eigen-gap is thatA is a "hub" matrix in the sense that it has dominant columns. Some applications of this hub theory in multiple-input and multiple-output (MIMO) wireless systems are presented.